Randomised Controlled Trial of Supported Employment in England: 2 year follow-up of the Supported Work and Needs (SWAN) Study - Peter Huxley (World Psychiatry, 2011)
The Individual Placement and Support (IPS) model is effective in helping individuals with severe and persistent mental illness gain competitive employment. We investigated the effectiveness and cost-effectiveness of IPS in England in patients followed up for 2 years. Patients with severe mental illness were randomised to IPS or local vocational services (treatment as usual). 219 participants were randomised, and 86% re-assessed 2 years later. Relatively low rates of competitive employment were found in both the intervention group and the treatment as usual group. Significantly more patients obtained work in the treatment arm (22% vs. 11%, p=0.041). There were no significant differences in costs. The employment rate among participants receiving IPS was lower than in previously published studies. This may reflect difficulties in the implementation of IPS where it is not structurally integrated into the community mental health team.